Genetic Pharmacotherapy - Rehan Haider (International Journal of Scientific Multidisciplinary Research, 2023)
In current drug development, proof-of-concept—determining whether a ligand engaging its target is likely to be therapeutic—requires specific ligands. This presents a catch-22, as the motivation to develop ligands requires proof-of-concept studies that cannot be conducted without ligands. A strategy we term genetic pharmacotherapy—a refinement of genetic blockade focused on drug-gable targets—obviates the catch-22 by enabling proof-of-concept studies before the development of specific ligands via genetic means in mouse models. In this strategy, which could help avert investment in molecular entities that will ultimately prove therapeutically efficacious, a gene is conditionally down-regulated via a molecular switch in adult mice. Both the precise temporal control of the intervention and the consequent change in the target protein function parallels the administration of drugs, with the additional advantage of perfect specificity. Moreover, genetic pharmacotherapy overcomes the impediment of the blood-brain barrier, which makes developing ligands for psychiatric disorders particularly challenging